OPTIMALISASI PERAN DAN FUNGSI MASJID DALAM KEGIATAN DAKWAH: STUDI KASUS DI MASJID BANDAR KLIPPA - Muhammad Hizbullah; Haidir; Syahrul Bakti Harahap; Yeltriana (Al-Manaj : Jurnal Program Studi Manajemen Dakwah, 2025)
This study aims to analyze the role and function of the Al-Muhajirin Mosque in Bandar Klippa Village in optimizing da'wah activities. The mosque as a religious institution not only functions as a place of ritual worship, but also plays an important role in the spiritual and social development of the community. Using descriptive qualitative methods, data were collected through observation, interviews, and documentation. The results of the study indicate that the Mosque Prosperity Council (DKM) has succeeded in implementing various da'wah programs such as routine religious studies, children's development, commemoration of Islamic holidays, and social activities such as eating together and village alms movements. Optimizing the function of this mosque shows the strategic role of the mosque in strengthening Islamic values, strengthening brotherhood, and empowering the community spiritually and socially. These findings can be a model for mosque empowerment in the context of local community-based da'wah